Analisis biaya dan waktu proyek renovasi area parkir rumah sakit AMC Cileunyi Kabupaten Bandung - Nurcahya, Said Bambang (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The purpose of this study was to analyze the cost and time of work in the AMC Hospital parking area. The research was carried out using a descriptive method by asking questions about current problems, so that a cost and time analysis was determined using the theories of the budget cost work schedule (BCWS), actual cost work performance (ACWP), and budget cost work performance (BCWP), and the use of the concept of earned value in evaluating project performance can be calculated by various factors that indicate the progress and performance of project implementation. The results of research on cost efficiency and time effectiveness used by contractors in working on parking area projects according to productivity and performance, cost index projections, and project final schedules use the Critical Ratio (CR): Schedule Performance Index (SPI) x Cost Performance Index (CPI).